2002
DOI: 10.1159/000048342
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Salmonella Infections: Meningitis, Subdural Collections and Brain Abscess

Abstract: Focal intracranial infections due to Salmonella are rare. So far, around 80 cases have been reported in the world literature. The authors present their experience of 6 cases of intracranial Salmonella infections, mainly subdural empyema in 5 and effusion in 1. In 1 case, subdural empyema was bilateral, and in another case, there was an associated brain abscess. Positive blood cultures and positive Widal tests were noticed in 2 patients each. Early diagnosis and prompt evacuation of subdural collections and bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 7 publications
0
28
0
1
Order By: Relevance
“…In addition to typical meningitis, focal intracranial infections with NTS can occur with or without meningitis. Principal among these are subdural empyema and brain abscess (178,213,232,236,328,337,404).…”
Section: Salmonella Speciesmentioning
confidence: 99%
“…In addition to typical meningitis, focal intracranial infections with NTS can occur with or without meningitis. Principal among these are subdural empyema and brain abscess (178,213,232,236,328,337,404).…”
Section: Salmonella Speciesmentioning
confidence: 99%
“…In most patients included in this study, the subdural effusion was bifrontoparietally located. Mahapatra et al [14] reported that subdural effusion was more frequently observed in the bifrontoparietal region, as reported in many studies.…”
Section: Discussionmentioning
confidence: 59%
“…Her general state was good, with no neurological signs or other accompanying symptoms. Of the blood tests performed on hospital admission, the following results are of interest: 12000 leucocytes per mm 3 , with 72% neutrophils and 8 mg/dl and C-reactive protein (CRP) (normal < 0.5 mg/dl). On suspicion of a possible complication of surgery, a cranial CT-scan was requested, which showed a fluid collection indicative of a right epidural parietal empyema ( Figure 1A).…”
Section: Case Presentationmentioning
confidence: 99%